MEDIA APLIKASI HEAGER (HEALTH TEENAGER) MENINGKATKAN PENGETAHUAN TENTANG MENARCHE - Siti Rofi'ah; Siti Chunaeni; Sri Utary Fepriyanti; Dwi Kuntari (Jurnal Sains Kebidanan, 2023)
Adolescent physical changes related to hormonal changes, the period of sexual maturity and reactions to menarche. Low understanding of menarche can have a negative impact on adolescent growth. Technological progress is a potential that can be used as a delivery of material related to menarche. The "Heager" application has several features, including video features and assessment features. The purpose of this study was to determine the effect of Heager application media on the level of knowledge about menarche. This study used a pre-experimental design study with a One-Group Pre Test-Post Test Design. Data analysis used the Wilcoxon test. The results showed that the average level of knowledge about menarche before using the heager application media was 13, after using the heager application media was 15. The results of the Wilcoxon test analysis obtained a p value 0.05. There is an influence of Heager application media on the level of knowledge about menarche. Most of the students who experienced an increase in knowledge were as many as 29 respondents. The conclusion of this study is that there is an effect of using Heager application media on the level of knowledge about menarche